MODE SATURATION, MODE COUPLING AND ENERGY HARVESTING FROM AMBIENT VIBRATION IN A PORTAL FRAME STRUCTURE - Balthazar, J. M. [UNESP]; Rocha, R. T. [UNESP]; Brasil, R. M.F.L.; Tusset, A. M.; de Pontes, B. R. [UNESP]; Silveira, M. [UNESP] (ASME International, 2014)
There has been much recent interest in the concepts of electro-mechanical systems that are able to scavenge, or harvest energy from their operating environment. Here, we present the extraction of energy from a simple portal frame structure excited via its second (first symmetric) mode. As 2:1 internal resonance is present between that mode and the first (sway) mode, the phenomenon of mode saturation and energy exchange (modal coupling) occurs. Energy pumped into the system through the second (vertical) mode is partially transferred to the horizontal (sway) mode. This paper presents results of numerical simulations of these phenomena and energy harvesting using a nonlinear piezoelectric material as a means of energy transduction. An evaluation of the energy available for harvesting in each of the considered modes is computed.